Loss of ACL function leads to alterations in tibial plateau common dynamic contact stress profiles. (16th August 2017) - Chen, Tony; Wang, Hongsheng; Warren, Russell; Maher, Suzanne
Abstract: It has been suggested that the repetitive nature of altered joint tissue loading which occurs after anterior cruciate ligament (ACL) rupture can contribute to the development of osteoarthritis (OA). However, changes in dynamic knee joint contact stresses after ACL rupture have not been quantified for activities of daily living. Our objective was to characterize changes in dynamic contact stress profiles that occur across the tibial plateau immediately after ACL transection. By subjecting sensor-augmented cadaveric knees to simulated gait, and analyzing the resulting contact stress profiles using a normalized cross-correlation algorithm, we tested the hypothesis that common changes in dynamic contact stress profiles exist after ACL injury. Three common profiles were identified in intact knees, occurring on the: (I) posterior lateral plateau, (II) posterior medial plateau, and (III) central region of the medial plateau. In ACL-transected knees, the magnitude and shape of the common dynamic stress profiles did not change, but their locations on the tibial plateau and the number of knees identified for each profile changed. Furthermore, in the ACL transected knees, a unique common contact stress profile was identified in the posterior region of the lateral plateau near the tibial spine. This framework can be used to understand the regional and temporal changes in joint mechanics after injury.